Yield, composition, and fatty acid profile of milk from Anglo Nubian goats fed a diet supplemented with vegetable oils - Toniolo Chavari, Andreia Cristina [UNESP]; Marques, Raquel Ornelas [UNESP]; Lara Canizares, Gil Ignacio; Brito, Evelyn Prestes [UNESP]; Barros Gomes, Helen Fernanda; Lourencon, Raquel Vasconcelos; Lima Meirelles, Paulo Roberto de [UNESP]; Goncalves, Heraldo Cesar [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2020)
We aimed to evaluate the inclusion of three sources of vegetable oil in the diet of lactating goats on production in 120 days of lactation and the effect of these sources and lactation stage on fortnightly composition and fatty acid profile of goat milk at 20, 50, 80, and 110 days of lactation. A completely randomized design was adopted and 32 Anglo Nubian goats were used, distributed in four treatments: control diet and diets with inclusion of 30 g/kg of dry matter of diet of canola, sunflower, or soybean oil. The dairy production was 182.75 kg, and there was no difference for treatments. Among the constituents, only urea nitrogen was influenced by treatment and presented lower content for control treatment. Day of lactation had an effect on lactose. Defatted dry extract and somatic cell count had a quadratic effect with minimum values around 100 and 33 days of lactation, respectively. The content of urea nitrogen, also with a quadratic effect, was higher at 93 days of lactation. For protein, there was an interaction between treatments and period and, at the end of lactation, its content was increased. The inclusion of vegetable oils promoted reduction in total saturated fatty acids (SFA) and increased the total content of monounsaturated fatty acids (MUFA) and conjugated linoleic acid. The proportions MUFA:SFA and PUFA:SFA, the atherogenicity and thrombogenicity indexes, and the relation hypocholesterolemic fatty acids:hypercholesterolemic fatty acids improved with oil addition in animal diets. The addition of vegetable oil to diets for lactating goats improve the fatty acid profile with no impairment on milk production and composition, and the milk from early stages of lactation has better nutritional quality of the lipid fraction.
Keywords: canola oil; dairy goat; fatty acids; lactation; ruminant nutrition